2018
DOI: 10.1016/j.jcp.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous Galerkin algorithms for fully kinetic plasmas

Abstract: We present a new algorithm for the discretization of the Vlasov-Maxwell system of equations for the study of plasmas in the kinetic regime. Using the discontinuous Galerkin finite element method for the spatial discretization, we obtain a high order accurate solution for the plasma's distribution function. Time stepping for the distribution function is done explicitly with a third order strong-stability preserving Runge-Kutta method. Since the Vlasov equation in the Vlasov-Maxwell system is a high dimensional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 65 publications
(98 reference statements)
1
87
0
Order By: Relevance
“…The five‐ and 10‐moment equation systems have been implemented in the finite‐volume version of the Gkeyll code, which uses a high‐resolution wave propagation method for the hyperbolic part of the equations and a point implicit method for the source terms (Hakim et al, ; Hakim, ), and has previously been used to study magnetic reconnection (Ng et al, , ; Wang et al, ). The kinetic simulations use the discontinuous Galerkin finite‐element Vlasov‐Maxwell solver of Gkeyll 2.0 (Juno et al, ). Because the Vlasov code uses a discontinuous Galerkin method, we require a basis function expansion in each cell, and we choose piecewise quadratic basis functions from the Serendipity Element family.…”
Section: Lower‐hybrid Drift Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The five‐ and 10‐moment equation systems have been implemented in the finite‐volume version of the Gkeyll code, which uses a high‐resolution wave propagation method for the hyperbolic part of the equations and a point implicit method for the source terms (Hakim et al, ; Hakim, ), and has previously been used to study magnetic reconnection (Ng et al, , ; Wang et al, ). The kinetic simulations use the discontinuous Galerkin finite‐element Vlasov‐Maxwell solver of Gkeyll 2.0 (Juno et al, ). Because the Vlasov code uses a discontinuous Galerkin method, we require a basis function expansion in each cell, and we choose piecewise quadratic basis functions from the Serendipity Element family.…”
Section: Lower‐hybrid Drift Instabilitymentioning
confidence: 99%
“…Because the Vlasov code uses a discontinuous Galerkin method, we require a basis function expansion in each cell, and we choose piecewise quadratic basis functions from the Serendipity Element family. Details on the particulars of the basis expansion can be found in Arnold andAwanou (2011) andJuno et al (2018).…”
Section: Simulations Of the Lhdimentioning
confidence: 99%
“…The simulation framework we will use for this study is Gkeyll, which includes solvers for continuum Vlasov‐Maxwell (Juno et al., ), gyrokinetics (Shi et al., ), and five and ten‐moment two‐fluid equations (Hakim, ; Hakim et al., ; Wang et al., ). In this work, we focus on the five‐ and ten‐moment two‐fluid models.…”
Section: The Five‐ and Ten‐moment Modelsmentioning
confidence: 99%
“…Prior Gkeyll reconnection studies (Ng et al., ; Wang et al., ) have demonstrated that k 0 α d α ∼1 is required to achieve agreement with PIC simulations, where subscript α refers to species. However, a value of 1/10 provides slightly better performance for turbulence simulations without significantly degrading the reconnection performance (Juno et al., ). Since we expect these event simulations to be turbulent, we choose closure parameters for both ten‐moment model simulations to be k 0 α d α =1/10.…”
Section: Initial Conditionsmentioning
confidence: 99%
“…A second class of kinetic algorithms is based on the propagation of the particle distribution function f in the sixdimensional position and velocity phase space x, y, z, v x , v y , v z , using the Boltzmann equation [e.g., 20] or the Vlasov equation in the collisionless case [e.g., [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. These methods do not suffer from statistical noise but they are significantly heavier due to the higher-dimensional space to be sampled.…”
Section: Introductionmentioning
confidence: 99%